Qualidade microbiológica, físico-química e atividade proteolítica do leite cru, após processamento térmico e durante sua vida de prateleira - Souza, Hâmara Milaneze de (2015)
The largest shelf life of industrialized milk is critical for the lactic supply chain, highlighting its quality both microbiological and physical chemistry, as well as its sensory aspects and its evolution during storage, especially UHT milk by offering significantly long time of storage. This study aims to evaluate the microbiological quality, physicochemical and proteolytic of milk coming from the process of fast pasteurization and UHT and its behavior during shelf life. For this study pasteurized milk samples were collected (1 dairy) and three of UHT milk (dairy 2). The microbiological analysis involved eight bacterial groups (aerobic mesophilic, total psychrotrophic, fecal coliforms, Staphylococcus spp., Bacillus cereus, Pseudomonas spp., Salmonella spp., Clostridium spp.) and have been made on raw milk, pasteurizer, and three shelf times in duplicate. The physico-chemical and proteolytic analyzes were made in the raw milk and in five different storage times. After pasteurization all samples remained within the limits stipulated by law for all microorganisms studied, however, the aerobic counts of mesophilic and psychrotrophic, dairy 1, 5 and 10 days did not differ statistically from raw milk, and the sample bottled referring to the day of collection resembles statistically with milk after pasteurization. All samples showed absence of microbial inhibitors. It was observed increase in casein macropeptide (CMP) levels in stored UHT milk, exceeding the given limit for direct consumption after 30 days of storage. The sedimentation mass also increased as the storage time increased. These results demonstrate that even though the pasteurized milk and UHT are within the required microbiological standards, the raw milk is still at high microbiological values. As same as UHT milk raw and initially present low concentrations of CMP, the content thereof gradually increases along the shelf life, probably because of proteases psychrotrophic bacteria